Therapeutic Effects of Natural Drugs on Alzheimer's Disease - Yuan Ma; Man-wen Yang; Xin-wei Li; Jian-wei Yue; Jun-zong Chen; Mei-wen Yang; Xuan Huang; Lian-lian Zhu; Fen-fang Hong; Shu-long Yang (Frontiers Media S.A., 2019)
Alzheimer disease (AD) is characterized as a chronic neurodegenerative disease associated with aging. The clinical manifestations of AD include latent episodes of memory and cognitive impairment, psychiatric symptoms and behavioral disorders, as well as limited activities in daily life. In developed countries, AD is now acknowledged as the third leading cause of death, following cardiovascular disease and cancer. The pathogenesis and mechanism of AD remain unclear, although some theories have been proposed to explain AD, such as the theory of β-amyloid, the theory of the abnormal metabolism of tau protein, the theory of free radical damage, the theory of the inflammatory response, the theory of cholinergic damage, etc. Effective methods to predict, prevent or reverse AD are unavailable, and thus the development of new, efficient therapeutic drugs has become a current research hot spot worldwide. The isolation and extraction of active components from natural drugs have great potential in treating AD. These drugs possess the advantages of multiple targets in multiple pathways, fewer side effects and a long duration of curative effects. This article summaries the latest research progress regarding the mechanisms of natural drugs in the treatment of AD, providing a review of the literature and a theoretical basis for improving the clinical treatment of AD.